Urban garden: case study of cultural Center of São Paulo - Rovaron, Amanda Tiemi; Pita, Juliano Veraldo da Costa (Revista Hipótese, 2020)
One of the most debated themes in the city of the 21st century is sustainability. In this scenario, agriculture and urban gardening stand out because they are strategies that reduce environmental impacts. The research "Urban Gardens: Case Study of the Cultural Center of São Paulo" seeks to understand the objective characteristics of the gardens, the historical, social context and its insertion in the urban complexity. Thus, an analysis is presented on the initiatives to take advantage of the urban voids, consolidated in the figure of the urban garden movements in a broad and multidisciplinary approach that allows to situate the question within the dynamics of the contemporary city.
Keywords: Urban Agriculture; Community Gardens; Sustaintability; Sao Paulo